2018
DOI: 10.1200/jco.2017.74.2940
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Novel Integrated Clinical-Genomic Risk Group Classification for Localized Prostate Cancer

Abstract: Purpose It is clinically challenging to integrate genomic-classifier results that report a numeric risk of recurrence into treatment recommendations for localized prostate cancer, which are founded in the framework of risk groups. We aimed to develop a novel clinical-genomic risk grouping system that can readily be incorporated into treatment guidelines for localized prostate cancer. Materials and Methods Two multicenter cohorts (n = 991) were used for training and validation of the clinical-genomic risk group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
127
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 169 publications
(131 citation statements)
references
References 30 publications
(29 reference statements)
4
127
0
Order By: Relevance
“…[29][30][31] The data from the current study also demonstrated a larger difference in OS compared with PCSM among these populations. Therefore, the current study data affirm NCCN guidelines indicating that caution should be applied when considering AS for men with favorable intermediate-risk disease as we await longer follow-up data regarding population-wide outcomes with AS.…”
Section: Discussionsupporting
confidence: 63%
“…[29][30][31] The data from the current study also demonstrated a larger difference in OS compared with PCSM among these populations. Therefore, the current study data affirm NCCN guidelines indicating that caution should be applied when considering AS for men with favorable intermediate-risk disease as we await longer follow-up data regarding population-wide outcomes with AS.…”
Section: Discussionsupporting
confidence: 63%
“…The overall pattern of greater proportions of regional and metastatic PCa in the elderly is an expected finding, at least in part: older men are less likely to be screened for PCa than their younger counterparts and are more likely to undergo PSA testing because of urinary symptoms. However, older men may also be more likely to present with metastatic disease because they are already at increased risk of having an undetected potentially lethal cancer, and this makes them more prone to metastases . Detecting these cancers at an earlier stage may have permitted curative therapy and the avoidance of metastatic spread.…”
Section: Discussionmentioning
confidence: 99%
“…The ASIRs shown here indicate that the absolute incidence of potentially lethal disease actually increases in men older than 70 years. The 10‐year metastasis rates for men with unfavorable intermediate‐risk disease and high‐risk disease are quite high . Men aged 70 to 75 years typically have estimated life expectancies longer than 10 years, and healthy men up to the age of 80 years can have life expectancies exceeding 10 years .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations